PERKEMBANGAN KINERJA GURU GEOGRAFI SMA DI KABUPATEN INDRAGIRI HULU PROVINSI RIAU STUDI TAHUN 2016 -2020 - ERLAN DA; Nofrion Nofrion (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) the development of performance based on research and scientific publications conducted 2) the development of teacher performance based on self-development 3) the development of teacher performance based on the innovative work done. This type of research is descriptive with a quantitative approach. The population of this study were all high school geography teachers in Indragiri Hulu Regency, Riau Province. The total population of this research is 18 teachers. Collecting data using questionnaires and documentation. The results of this study found that 1) The general identity of high school geography teachers in Indragiri Hulu Regency for the last five years (2016-2020) has been good, seen from the latest education of all high school geography teachers who have met the predetermined criteria 2) Research and scientific publications of high school geography teachers in Indragiri Hulu Regency for the last five years (2016-2020) was classified as very low because of the three indicators discussed, 50% of the teachers were involved in research and scientific publications. 3) The self-development of high school geography teachers in Indragiri Hulu Regency is still low with a percentage of 24%. 4) The innovative work of the geography teacher Indragiri Hulu is still low because no teacher is involved in innovative